Pengaruh Pemberian Kitosan Cangkang Udang Putih (Penaeus merguiensis) terhadap Ketebalan Trabekular Femur Tikus Wistar Betina Pasca Ovariektomi (The Effect of White Shrimp (Penaeus merguiensis) Shells Chitosan on the Trabecular Thickness of Femoral Fem - Suci Rizalah I; Muhammad Hasan; Septa Surya Wahyudi (Pustaka Kesehatan, 2016)
There are low bone density and defects in bone micro-architecture which led to a significant increases of bone fragility and bone fracture in osteophorosis, due to an oestrogen deficiency in post-menopause woman. Natural polymer which has potential action on bone remodelling is chitosan. Chitosan can reduce the production of IL-1, IL-6, TNF-α and PGE2 osteoclast cell as well as increase osteoblast cell differentiation in bone formation process. The study aimed to determine the effect of chitosan white shrimp shell on the trabecular thickness of femur female wistar rats post-ovariectomy. This research was the quasy experimental laboratory research using female wistar rats that were divided into three groups; a non-ovariectomy as control, a negative ovariectomy, and an ovariectomy treatment group that was given chitosan 0,05 g/day. After 14 days, the experimental mice were euthanized and trabecular thickness was measured. There were 59,53µm, 32,44µm and 78,43µm trabecular thickness in the control group, the negative control group and the treatment group, respectively. The data were analysed using one way ANOVA and they showed a significant differences between all groups (p=0,000). It can be concluded that the chitosan of white shrimp shell can significantly increase trabecular thickness femur female wistar rats post-ovariectomy. Keywords: Osteoporosis, Chitosan, Ovariectomy, Trabecular Thickness